Synthesis and characterization of surface modified nano-silica for the separation of oil and water - Shahrin bin Dzainal, Shahrin (2009)
This document is based on the research project entitled `Synthesis and Characterization of Surface Modified Nano-Silica for the Separation of Oil and Water'. The project is basically on the preparation of surface modified silica in nano particle size to be use in oil-water separation.